2006
DOI: 10.2298/mpns0610456j
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain and degenerative disc disease

Abstract: Coservative treatment consists of rest, physical therapy, pharmacological therapy and injection therapy. Physical rehabilitation with active patient participation is a key approach to treatment of patients with discogenic pain. Physical therapy, occupational therapy and kinesitherapy are important for improving muscle strength, endurance, and flexibility. Disc surgery is performed if surgical intervention is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Disc degeneration occurs from a variety of contributory factors. Apoptosis, collagen abnormality, aging, vascular supply anomaly, mechanical stress, inflammation, abnormal proteoglycan and possible genetic factors all of which may contribute to disc degeneration [33,36] . We have observed that frequency of disc degeneration increased with increasing age group in this study group.…”
Section: Discussionmentioning
confidence: 99%
“…Disc degeneration occurs from a variety of contributory factors. Apoptosis, collagen abnormality, aging, vascular supply anomaly, mechanical stress, inflammation, abnormal proteoglycan and possible genetic factors all of which may contribute to disc degeneration [33,36] . We have observed that frequency of disc degeneration increased with increasing age group in this study group.…”
Section: Discussionmentioning
confidence: 99%
“…and the causes (intervertebral disc stimulation, vertebral inflammation or endplate inflammation, intraspinal or posterior peritoneal disease, etc.). Therefore, using myofascial electrothermal acupuncture or radiofrequency to release the muscle fascia of the compression nerve [24], or using the intervertebral foramen to release the posterior occlusion of the spinal nerve [25] to remove the sources of compression nerve which caused low back pain was the best way to treat pain.…”
Section: Stimulaltion Of the Sensory Nerve Endings Often Causes Local Painmentioning
confidence: 99%
“…Due to its frequency and correctibility, postural scoliosis is a genuine subject of interest and work of educators and teachers of physical culture and sport in schools (Jovović, 2008). Compensatory scoliosis is caused by a static disorder (leg length discrepancy, muscle spasm, congenital hip dislocation, pain related to spinal disc herniation) (Jandrić & Antić, 2006). Structural scoliosis is characterised by a change in the structure and morphology of vertebral body.…”
Section: Postural Disorders and Scoliosismentioning
confidence: 99%